Senam Ayo Bangkit Senam Ayo Bangkit Training Can Increase Physical Fitness Reviewed From Maximum Oxygen Volume (VO2Max) - Astrawan, I Putu; Prisa Jaya, I Putu (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2021)
Physical training has an important role in maintaining and increasing the degree of physical fitness seen from the VO2Max ability. The aim of the study was to find out that let's rise up can improve physical fitness in terms of VO2Max. This type of experimental research was the randomized pretest posttest control group design. The sample of this study was that of 22 students of the Physiotherapy Study Program divided into 2 groups. Group 1 was given a let's get up and group 2 as a control group, with a frequency of training 3 times a week for 6 weeks. VO2Max was measured by the Bleeps Test (MFT) instrument. The normality and homogeneity tests of the data show that the data distribution is normal and homogeneous. The mean intra-group difference test VO2Max was tested by using t-paired test. Different test results with t-paired before and after training, Group 1 and Group 2 were significantly different (p <0.05). The VO2Max test results between the two groups before and after the training were tested by t-independent sample test. The mean VO2Max in the two groups before training was p = 0.21 (p> 0.05) and after training p = 0.00 (p <0.05). In Group 1, the mean VO2Max (L / m) before training was 26.34 and the mean after training was 35.48 with a difference of 9.14 and an increase in percentage of 34.70%. Whereas in Group 2, the mean VO2Max before training was 25.36 and the mean after training was 27.42 with a difference of 2.06 and an increase of 8.12%. This shows that the treatment of group 1 and group 2 both had an effect. However, the increase in group 1 was better than group 2. It can be concluded that the let's get up exercise training can improve physical fitness in terms of VO2Max.